2015
DOI: 10.1016/j.jnnfm.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dynamics of a viscoelastic film subjected to a spatially periodic electric field

Abstract: We investigate the non-linear dynamics of the electrohydrodynamic instability of a viscoelastic polymeric film under a patterned mask. We develop a computational model and carry out 2D numerical simulations fully accounting for the flow and electric field in both phases. We perform a thorough parametric study and investigate the influence of the various rheological parameters, the applied voltage and the period of the protrusions of the mask in order to define the fabrication limits of this process in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The set of algebraic equations is integrated in time with the implicit Euler method. The model has been implemented in COMSOL Multiphysics ® commercial software and has been cross-checked against our in-house FEM solver [73].…”
Section: Numerical Implementationmentioning
confidence: 99%
“…The set of algebraic equations is integrated in time with the implicit Euler method. The model has been implemented in COMSOL Multiphysics ® commercial software and has been cross-checked against our in-house FEM solver [73].…”
Section: Numerical Implementationmentioning
confidence: 99%
“…The influences of some process parameters, such as voltage, air gap, polymer properties, on the polymeric behavior have been well studied. Some conclusions have been revealed as guidance for a faithful structure . It is revealed that the large voltage, the small air gap, and the polymer with a large dielectric permittivity can generate a large L‐DEP pressure to promote the conformal deformation .…”
Section: Introductionmentioning
confidence: 99%
“…Karapetsas & Bontozoglou (2015) carried out 2D numerical calculations for a Newtonian fluid and a viscoelastic polymeric fluid under a patterned mask to find that perturbations grow until they reach the top electrode and viscoelasticity affects their wavelength.…”
Section: Introductionmentioning
confidence: 99%